Papers and originals. Issue 6013 (3rd April 1976) - Rogers, D; Tripp, J; Bentovim, A; Robinson, A; Berry, D; Goulding, R
Abstract : Six cases of persistent non-accidental poisoning of children by their parents are reported. Certain features may draw attention to the diagnosis, particularly bizarre symptoms and signs with no apparent pathological explanation, and toxicological analysis should be carried out to obtain rapid confirmation of the diagnosis. The underlying disorder may include marital conflict, overinvolvement between parent and child, or drug abuse in the parents. A suggested plan of action for managing this problem is outlined.